2018
DOI: 10.1021/acs.chemrestox.8b00112
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Outcome Pathway-Driven Analysis of Liver Steatosis in Vitro: A Case Study with Cyproconazole

Abstract: Adverse outcome pathways (AOPs) describe causal relationships between molecular perturbation and adverse cellular effects and are being increasingly adopted for linking in vitro mechanistic toxicology to in vivo data from regulatory toxicity studies. In this work, a case study was performed by developing a bioassay toolbox to assess key events in the recently proposed AOP for chemically induced liver steatosis. The toolbox is comprised of in vitro assays to measure nuclear receptor activation, gene and protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 57 publications
(128 reference statements)
5
63
1
Order By: Relevance
“…Altogether, these findings indicate that pesticides affect several processes that result in oxidative stress: the CYP450 system, mitochondrial respiration, antioxidant pathways, the stress adaptor system, and scavenger ROS activity. Besides oxidative stress, pesticide exposure may lead to NAFLD through their impact on lipid metabolism by (i) modifying fatty acid uptake and efflux [171] and modulating FFA transport as described for insecticides and herbicides, (ii) increasing lipogenesis ( [173,406] (Table 1), (iii) altering oxidation pathways [175]; insecticides, herbicides, and fungicides affect both β-oxidation and lipogenesis (Tables 1 and 2), (iv) interacting with nuclear receptors [416][417][418][419][420][421] involved in the control of metabolism as demonstrated for pyrethroid and neonicotinoid insecticides [176][177][178], and imidazole or triazole fungicides [158,382] or a pesticide mixture [193], but implication in NAFLD is not proven. Some pesticides may ameliorate lipid metabolism.…”
Section: Oxidative Stress In Nafld: Role Of Pesticidesmentioning
confidence: 99%
“…Altogether, these findings indicate that pesticides affect several processes that result in oxidative stress: the CYP450 system, mitochondrial respiration, antioxidant pathways, the stress adaptor system, and scavenger ROS activity. Besides oxidative stress, pesticide exposure may lead to NAFLD through their impact on lipid metabolism by (i) modifying fatty acid uptake and efflux [171] and modulating FFA transport as described for insecticides and herbicides, (ii) increasing lipogenesis ( [173,406] (Table 1), (iii) altering oxidation pathways [175]; insecticides, herbicides, and fungicides affect both β-oxidation and lipogenesis (Tables 1 and 2), (iv) interacting with nuclear receptors [416][417][418][419][420][421] involved in the control of metabolism as demonstrated for pyrethroid and neonicotinoid insecticides [176][177][178], and imidazole or triazole fungicides [158,382] or a pesticide mixture [193], but implication in NAFLD is not proven. Some pesticides may ameliorate lipid metabolism.…”
Section: Oxidative Stress In Nafld: Role Of Pesticidesmentioning
confidence: 99%
“…Initial 2 weeks of cultivation in William's E medium (Pan-Biotech GmbH, Aidenbach, Germany) containing 10% fetal calf serum (FCS) (PAN-Biotech GmbH, Aidenbach, Germany), 100 U/mL penicillin, 100 µg/mL streptomycin, 0.05% human insulin (all from PAA Laboratories GmbH, Pasching, Austria) and 50 µM hydrocortisone-hemisuccinate (Sigma-Aldrich, Taufkirchen, Germany) were followed by a 2-week differentiation phase. The differentiation medium contained 1.0% DMSO (days 1-3) and later 1.7% DMSO (days 4-14), in addition to the aforementioned supplements (Gripon et al 2002;Luckert et al 2018). Treatment of HepaRG cells with cyproconazole or prochloraz was then performed for 24 h in phenol red-free William's E medium (Pan-Biotech GmbH, Aidenbach, Germany) which contained all ingredients as the differentiation medium including a final DMSO concentration of 1.7%, but only 2% FCS.…”
Section: In Vitro Samplesmentioning
confidence: 99%
“…The assays were performed as previously described by Luckert et al (2018). Plasmids, plasmid amount and positive controls were also used as described in the aforementioned paper.…”
Section: Dual-luciferase Reporter Assaymentioning
confidence: 99%
“…Therefore, analysis of triglyceride accumulation was performed using combinations of steatotic and non-steatotic substances in the human hepatocarcinoma cell line HepaRG. Previous studies already revealed that HepaRG cells are an appropriate model to study steatosis in vitro (Antherieu et al 2010;Knebel et al 2019a;Lasch et al 2020a;Luckert et al 2018;Tanner et al 2018;Tolosa et al 2016). The following test substances were chosen: fludioxonil (FDO) as a non-steatotic substance, as well as difenoconazole (DIF), propiconazole (PPC) and tebuconazole (TBC) as steatotic substances.…”
Section: Introductionmentioning
confidence: 99%